Novel Quantum Dot-Ionogel Light Emitting Devices and a Determination of the Mechanism for Electroluminescence. - Nash, Jared H. (Tufts Archival Research Center, 2014)
Abstract: Colloidal quantum dots are an emerging class of nanomaterials beginning to be implemented into commercial displays. Companies such as Sony, QD Vision, and Apple are all currently researching quantum dot display technologies. Quantum dots are semiconducting nanoparticles that emit very saturated colors which make them ideal for displays. This research used colloidal quantum dots and a room temperature ionic liquid suspended in a polymer matrix (ionogel) to create a novel light emitting device architecture. The originally proposed mechanism for this device was to use the ionic liquid in the ionogel to create a large electric field around the quantum dots, causing the quantum dots to self-ionize and emit light. This new device architecture proved to be versatile, using both AC and DC biases. The peak wavelength of the electroluminescence was 612 nm and the emission spectra had a full width half peak of 30 nm; therefore, these devices emitted a saturated red color. The external quantum efficiency was calculated to be approximately 0.002%. These devices were operational in ambient conditions and were stable over a period of at least 3.5 hours. Because the devices were operational using a DC bias, the mechanism for electroluminescence could not be the originally proposed mechanism. Device functionality most likely involved a redox reaction with water vapor being one of the reactants. Future work should be performed to determine the reaction responsible for electroluminescence, and to improve the efficiency of light emission.